2001
DOI: 10.1046/j.1442-2042.2001.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal cyst: A review of the Japanese literature and report of a case

Abstract: Adrenal cysts are a rare condition and are usually non-functioning and asymptomatic. A 44-yearold man was referred from another hospital because a left retroperitoneal tumor was incidentally found by abdominal echography. Laboratory findings including adrenal hormonal study were within the normal range. It showed homogeneously low intensity on T 1 -weighted images and high intensity on T 2 -weighted images on magnetic resonance imaging (MRI). Angiography demonstrated that the tumor was avascular and of left ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
0
16
0
3
Order By: Relevance
“…Foster classified adrenal cysts into four categories and Tanuma et al recently reported the frequency of each category in Japan (Table 5). [6] Pseudocysts are most common (62.9%), and parasitic cysts, which are mainly caused by the echinococcal infection, are not reported yet in Japan. As our case underwent no invasive examinations, the histological diagnosis remained unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Foster classified adrenal cysts into four categories and Tanuma et al recently reported the frequency of each category in Japan (Table 5). [6] Pseudocysts are most common (62.9%), and parasitic cysts, which are mainly caused by the echinococcal infection, are not reported yet in Japan. As our case underwent no invasive examinations, the histological diagnosis remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Foster, [9] Tanuma et al* [6] In general, these diagnostic tools can differentiate cystic lesion from solid mass and define its origin. But it sometimes becomes difficult when the mass lesion is large and its content does not show the typical feature of uncomplicated cyst.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On ultrasound (US), ACL is a well-marginated, anechoic lesion typically located on the suprarenal area and which can show shadows and internal echoes, when calcifications or internal debris are present [1][2][3][4][5][6][7]. On CT scan the mass is identified as a hypodense, non-enhanced lesion with smooth borders and thin wall (<3,5 mm).…”
Section: Case Reportmentioning
confidence: 99%
“…However, symptoms can occasionally occur and they are typically related to the overall mass of the cyst. The most common symptoms are abdominal or flank pain, gastrointestinal discomfort, palpable mass and arterial hypertension and palpitation especially in functional cysts [5,6].…”
Section: Case Reportmentioning
confidence: 99%